Hydrochlorothiazide use is strongly associated with risk of lip cancer. (6th June 2017) - Pottegård, A.; Hallas, J.; Olesen, M.; Svendsen, M. T.; Habel, L. A.; Friedman, G. D.; Friis, S.
Abstract: Background: The diuretic hydrochlorothiazide is amongst the most frequently prescribed drugs in the United States and Western Europe, but there is suggestive evidence that hydrochlorothiazide use increases the risk of lip cancer. Objectives: To study the association between use of hydrochlorothiazide and squamous cell carcinoma of the lip. Methods: We conducted a case–control study using Danish nationwide registry data. From the Cancer Registry (2004–2012), we identified 633 case patients with squamous cell carcinoma (SCC) of the lip and matched them to 63 067 population controls using a risk‐set sampling strategy. Hydrochlorothiazide use (1995–2012) was obtained from the Prescription Registry and defined according to cumulative use. Applying conditional logistic regression, we calculated odds ratios (ORs) for SCC lip cancer associated with hydrochlorothiazide use, adjusting for predefined potential confounders obtained from demographic, prescription and patient registries. Results: Ever‐use of hydrochlorothiazide was associated with an adjusted OR for SCC lip cancer of 2.1 (95% confidence interval (CI): 1.7–2.6), increasing to 3.9 (95%CI: 3.0–4.9) for high use (≥25 000 mg). There was a clear dose–response effect ( P < 0.001), with the highest cumulative dose category of hydrochlorothiazide (≥100 000 mg) presenting an OR of 7.7 (95%CI: 5.7–10.5). No association with lip cancer was seen with use of other diuretics or nondiuretic antihypertensives. Assuming causality, we estimated that 11% of the SCC lip cancer cases could be attributed to hydrochlorothiazide use. Conclusions: Hydrochlorothiazide use is strongly associated with an increased risk of lip cancer.